2011
DOI: 10.1007/s00405-011-1668-x
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear hearing loss in patients with Laron syndrome

Abstract: The aim of this prospective clinical study was to test auditory function in patients with Laron syndrome, either untreated or treated with insulin-like growth factor I (IGF-I). The study group consisted of 11 patients with Laron syndrome: 5 untreated adults, 5 children and young adults treated with replacement IGF-I starting at bone age <2 years, and 1 adolescent who started replacement therapy at bone age 4.6 years. The auditory evaluation included pure tone and speech audiometry, tympanometry and acoustic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Neurosensorial hearing loss is a quite common finding in children with perinatal problems and also in children with alterations in GH secretion or its signaling pathways [87,88]. We treated with GH and specific auditory stimulation a child with cerebral palsy, The patient at admission.…”
Section: Ghd and Nervous System Functioningmentioning
confidence: 99%
“…Neurosensorial hearing loss is a quite common finding in children with perinatal problems and also in children with alterations in GH secretion or its signaling pathways [87,88]. We treated with GH and specific auditory stimulation a child with cerebral palsy, The patient at admission.…”
Section: Ghd and Nervous System Functioningmentioning
confidence: 99%
“…In humans, patients with Laron syndrome treated preventively with IGF-1 develop normal hearing [89]. It has been demonstrated that topical application of IGF-1 in the round window, prior tympanostomy, of patients with sudden hearing loss is a safe and effective therapy with minor side effects for those patients in whom initial treatment Fig.…”
Section: Igf-1mentioning
confidence: 99%
“…In human beings, SNHL occurs in patients with mutations in Igf1 gene (Woods et al, 1996; Bonapace et al, 2003; Walenkamp et al, 2005), primary IGF-1 deficiency (Attias et al, 2012), or low serum IGF-1 levels due to other genetic defects (Barrenas et al, 2000; Johnson et al, 2007), indicating the importance of IGF-1 in hearing. Replacement therapy using recombinant IGF-1 rescues patients from the hearing loss in Laron syndrome (Attias et al, 2012). The SNHL in Laron syndrome patients is attributed to cochlear dysfunction, based on otoacoustic emission test results (Attias et al, 2012).…”
Section: Igf-1 and The Inner Earmentioning
confidence: 99%
“…Replacement therapy using recombinant IGF-1 rescues patients from the hearing loss in Laron syndrome (Attias et al, 2012). The SNHL in Laron syndrome patients is attributed to cochlear dysfunction, based on otoacoustic emission test results (Attias et al, 2012). However, in a mouse model of IGF-1 deficiency, that is in IGF-1 knockout mice (Camarero et al, 2001, 2002; Cediel et al, 2006; Riquelme et al, 2010), the causes of SNHL were reported as the loss of spiral ganglion neurons, abnormal myelination of the cochlear nerve, and degeneration of the stria vascularis, based on the results of morphological (Camarero et al, 2001, 2002) and auditory brain stem response studies (Cediel et al, 2006; Riquelme et al, 2010).…”
Section: Igf-1 and The Inner Earmentioning
confidence: 99%